Manajemen Badan Usaha Milik Desa ( BUMDes) “Berkah Banyu Makmur” Di Desa Pancasan Kecamatan Ajibarang Kabupaten Banyumas - kholisoh, kholisoh; sutikno, Chamid; Nastiti, Dian; Amanda, Ariesta; Permana Pribadi, Indah Ayu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research examines the Management of Village-Owned Enterprises (BUMDes) "Berkah Banyu Makmur" in Pancasan Village, Ajibarang District, Banyumas Regency. The research method used is qualitative with descriptive analysis. Using primary and secondary data collected through observation, interviews and documentation. The management theory used is the George R. Terry, Leslie W. Rue, G. A. Ticolau model, with its 4 aspects, namely: Planning, Organizing, Actuating, and Controlling. The research results show that BUMDes "Berkah Banyu Makmur" has succeeded in implementing management functions well. The planning aspect involves village deliberations and regulations for business development as well as efforts to make Pancasan an Edutourism Village. The organizational aspects are clear and structured, as well as the development of BUMDes using the hexahelix model. Aspects of implementing BUMDes' daily operational activities have been regulated and structured with individual and team duties and responsibilities. Routine monitoring and evaluation aspects to ensure goals are achieved, with monthly and daily monitoring. With continuous efforts and strong commitment to the vision of becoming an Edutourism Village, it is hoped that this BUMDes can continue to develop and provide greater benefits for the people of Pancasan Village, as well as becoming an inspiring example for BUMDes in the surrounding area.